Insulin, Aging, and the Brain: Mechanisms and Implications - Akintola, Abimbola A.; van Heemst, Diana (Frontiers in Endocrinology, 2015)
There is now an impressive body of literature implicating insulin and insulin signaling in successful aging and longevity. New information from in vivo and in vitro studies concerning insulin and insulin receptors has extended our understanding of the physiological role of insulin in the brain. However, the relevance of these to aging and longevity remains to be elucidated. Here, we review advances in our understanding of the physiological role of insulin in the brain, how insulin gets into the brain, and its relevance to aging and longevity. Furthermore, we examine possible future therapeutic applications and implications of insulin in the context of available models of delayed and accelerated aging.